If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 = -6x + -10 Reorder the terms: 26 = -10 + -6x Solving 26 = -10 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 26 + 6x = -10 + -6x + 6x Combine like terms: -6x + 6x = 0 26 + 6x = -10 + 0 26 + 6x = -10 Add '-26' to each side of the equation. 26 + -26 + 6x = -10 + -26 Combine like terms: 26 + -26 = 0 0 + 6x = -10 + -26 6x = -10 + -26 Combine like terms: -10 + -26 = -36 6x = -36 Divide each side by '6'. x = -6 Simplifying x = -6
| -3x+7=34 | | 10n-6=64 | | 6x^2+x+9=0 | | 7-9x=7x-19 | | x^3-8x-5=0 | | -10x-20=-220 | | 7x-49=0 | | 10n-6x=64 | | -16x^2+40x=0 | | -8(-8)=x | | 13-x=9 | | 10r+8=28 | | 2.3g=7.3 | | -65=7+6x | | 5x-120=0 | | 3x-(-2)=15 | | 8x+12=-164 | | -4x+64=0 | | -3x-6y-4x+8y= | | 3x+21=0 | | 5b-2=2(3b-4) | | 141-2x=6x+21 | | y=9+x | | 0.33k-4=9 | | 0.3k-4=9 | | 2d+24-14=84 | | 11x-7=7x+3 | | 11x-9=7x | | 12-(-8x)+2x-(-9)= | | 3(3+4x)=15x | | 5+6x=29 | | 45-7x=3 |